Association of obesity and LDL subfractions evaluated by body mass index, waist circumference, and diabetes status: the ELSA-Brasil study - Eugenio G. Moraes; Giuliano Generoso; Isabela M. Bensenor; Raul D. Santos; Itamar S. Santos; Alessandra C. Goulart; Steven R. Jones; Krishnaji R. Kulkarni; Michael J. Blaha; Peter P. Toth; Paulo A. Lotufo; Marcio Sommer Bittencourt (Diabetology & Metabolic Syndrome)
Abstract Low-density lipoproteins (LDL) comprise a pool of particles with different densities that may have variable impact on atherogenesis. Studies suggest that obese individuals with elevated body mass index (BMI) and waist circumference (WC) have increased small and dense LDL subfractions (sdLDL-c). It is unclear if diabetes (T2D) and insulin resistance (IR) may modify this association. We included 4,111 (50.4 ± 8.6 years of age, 45.5% men) individuals with neither prior cardiovascular disease nor use of lipid-lowering medications. Total LDL-c and its subfractions (LDL1-c, LDL2-c, LDL3-c, and LDL4-c) were measured by vertical zonal ultracentrifugation. We considered the subfractions LDL1-c and LDL2-c as large buoyant LDL (lbLDL-c) and the subfractions LDL3-c and LDL4-c as sdLDL-c. We analyzed the association between LDL-c subclasses, BMI and WC using linear regression analysis and stratified by the presence of T2D and IR. For sdLDL-c, a direct association with hypertension, T2D, fasting plasma glucose, total cholesterol, LDL-c, and triglycerides was observed. In multivariate analysis, after adjustment for age, sex, race and triglycerides, the strong association of sdLDL-c with BMI (β 95% CI 0.16 (0,13–0,19)) and WC (β 95% CI 0.22 (0.19–0.26)) persisted. After stratification, the association of sdLDL-c and WC was present only in those with insulin resistance or diabetes. BMI showed a smaller impact than WC on this association. WC and BMI were strongly associated with sdLDL-c subfractions. Further, this association was modified by diabetes and insulin resistance status.